Proporsi dan Alasan Pengunaan Buah Lokal dan Non Lokal Bali dalam Upacara Keagamaan Pura Kahyangan Tiga di Desa Pakraman Sebali Kecamatan Tegallalang, Kabupaten Gianyar - SAPUTRA, I WAYAN YOGA WIRA; SUARDI, I DEWA PUTU OKA; WINDIA, WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.4, Oktober 2018DO - 10.24843/JAA.2018.v07.i04.p15, 2018)
Proportion and Reasons of Using Bali's Local and Non Local Fruits in Religious Ceremony of Pura KahyanganTiga in the Pakraman Village of Sebali, Tegallalang Sub-District of Gianyar Regency Pakraman Village of Sebali is a village located in Keliki Village, Tegallalang Subdistrict, of Gianyar Regency. The number of non-local fruits affect the use of fruits in the religious ceremonies in Pakraman Village of Sebali. The purpose of this study was to investigate the reasons for the use of local and non-local fruits as a means of religious rituals in the Pakraman Village of Sebali. The use of local and non-local Balinese fruits in Sebali Pakraman Village, Tegallalang Subdistrict, Gianyar regency, with the average comparison of the total use of local fruit with non-local Bali fruit per kg was 14.72: 13 with average price comparison of 208.059: 465.930 or 53.08%: 46.88%. With the use of fruits in each temple, namely, Pura Desa for 7.5 kg with a value of Rp 104.699 for local fruit, and 6.42 kg with a value of Rp 223.263.3 for nonlocal fruit. Pura Puseh by 3.23 kg with value Rp 42.889,3 for local fruit and 3.03 kg with value Rp 108.000 for non-local fruits. Pura Dalem by 3.99 kg with a value of Rp 55,099 for local fruits and 3.56 kg with a value of Rp 134,666. Housewives are expected to encourage the development of local fruit cultivation and support local fruit farmers.